Risk-Based Capital, Premium Income, and Financial Performance Effects on Indonesian Insurers’ Profitability: Pengaruh Risk-Based Capital, Pendapatan Premi, dan Kinerja Keuangan terhadap Profitabilitas Perusahaan Asuransi di Indonesia - Suryani Suryani; Febriyanti Febriyanti; Reza Hardian Pratama (International Journal of Business and Quality Research, 2026)
This study aims to analyze the effect of Risk Based Capital (RBC), premium income, and Comparative Financial Performance (CFP) proxied by the loss ratio on the profitability of insurance companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using panel data regression analysis. The estimation model applied in this study is the Common Effect Model (CEM), selected based on model selection procedures. The data used are secondary data obtained from the annual financial statements of insurance companies. The results indicate that partially, RBC has a significant effect on profitability, premium income does not have a significant effect on profitability, andCFP, measured by the loss ratio, has a significant effect on profitability. Simultaneously, RBC, premium income, and CFP jointly have a significant effect on profitability. The Adjusted R-squared value suggests that the model’s explanatory power is relatively limited, indicating that other factors outside the model also influence the profitability of insurance companies. These findings imply that the profitability of insurance companies is not solely determined by premium income but is also influenced by capital adequacy management and claims risk control. Therefore, insurance companies are encouraged to strengthen risk management practices and operational efficiency in order to enhance sustainable financial performance.